2021
DOI: 10.3389/fcimb.2021.609160
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Coronavirus Interacts With Endogenous Retrotransposon in Human Cells

Abstract: There is an increased global outbreak of diseases caused by coronaviruses affecting respiratory tracts of birds and mammals. Recent dangerous coronaviruses are MERS-CoV, SARS-CoV, and SARS-CoV-2, causing respiratory illness and even failure of several organs. However, profound impact of coronavirus on host cells remains elusive. In this study, we analyzed transcriptome of MERS-CoV, SARS-CoV, and SARS-CoV-2 infected human lung-derived cells, and observed that infection of these coronaviruses all induced increas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 56 publications
(74 reference statements)
1
44
0
4
Order By: Relevance
“…In some cases, the resulting chimeric cDNAs were integrated without the generation of a target site duplication ( 29 ). A recent study has also suggested that the interaction between coronavirus sequences and endogenous retrotransposon could be a potential viral integration mechanism ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, the resulting chimeric cDNAs were integrated without the generation of a target site duplication ( 29 ). A recent study has also suggested that the interaction between coronavirus sequences and endogenous retrotransposon could be a potential viral integration mechanism ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous LINE1 elements have been shown to be expressed in aged human tissues ( 35 ) and LINE1-mediated somatic retrotransposition is common in cancer patients ( 36 , 37 ). Moreover, expression of endogenous LINE1 and other retrotransposons in host cells is commonly up-regulated upon viral infection, including SARS-CoV-2 infection ( 38 40 ).…”
mentioning
confidence: 99%
“…Human-SARS-CoV-2 Chimeric Reads in RNA-seq Libraries of SARS-CoV-2 Infected Cell Lines Chimeric reads between human and SARS-CoV-2 RNA have been identified in RNA-seq data from infected cells in two recent studies (Zhang et al, 2020;Ying et al, 2021), presumed to be transcribed from reversed transcribed SARS-CoV-2 RNA integrated into the host DNA. To confirm these findings and exclude alternative origins of virus-host chimeric reads, we analyzed public RNA-seq datasets of cells infected with unrelated RNA viruses or SARS-CoV-2, and lung samples from a coronavirus disease 2019 (COVID-19) patient and a healthy control, using a standard pipeline, also used in the previous studies (Zhang et al, 2020;Ying et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Since detection of such chimeric reads in RNA-seq data would require transcription of the somatic integration, it would likely underestimate the total number of integrations. The high frequency of expressed somatic SARS-CoV-2 integrations reported (Zhang et al, 2020;Ying et al, 2021) was, therefore, unexpected. However, the majority of chimeric human-SARS-CoV-2 RNA reads may have a different origin.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation